Peculiarities of Central and Peripheral Changes at Onset of Dosed and Maximal Exercise Tests - Birutė Zacharienė; Jonas Poderys; Eugenijus Trinkūnas; Alfonsas Buliuolis (Lithuanian Sports University, 2018)
Research background and hypothesis. Since varying types of physical workloads activate different physiological system activity at different degree, during dosed and maximal exercises the total effects can highlight the properties of central and peripheral mechanisms and reveal significant synergies between the central and peripheral cardiovascular processes. Research aim was to determine the peculiarities of central and peripheral indices of cardiovascular system while performing dosed and maximal exercise tests. Research methods. Two groups took part in the study - sportsmen-sprinters (16) and sportsmen - endurance group (11). The participants of the study performed Roufier exercise and 30 s maximal jump test with maximal efforts. The 12-leads ECG was registered continuously and the changes of heart rate (HR), JT interval and ratio JT/ RR were analysed. Near-infrared spectroscopy was employed for continuous registration of the changes in oxygen saturation (StO 2 ) and arterial blood flow. Research  results.  The  results  obtained  during  the  study  showed  increasingly  changing  ECG  indices  while performing exercise load in both athlete groups but there was no statistically significant difference between groups while performing maximal exercise, thus oxygen saturation and arterial blood flow was statistically significantly faster and decreased more in sprint athlete group. Discussion  and  conclusion.  Dosed  and  maximal  exercise  test  indicated  the  peculiarities  of  cardiovascular function of athletes, although more differences between individual peculiarities of athletes can be revealed while performing a dosed exercise test and still more differences - while the maximal exercise tests are performed and during the recovery after exercising. Keywords: dosed and maximal exercise test, cardiovascular system, endurance, sprint.